Micah an international theological commentary - Gignilliat, Mark S. 1976- (London T&T Clark, 2019)
In this International Theological Commentary on the book of Micah, Mark S. Gignilliat begins by reflecting upon the nature of such commentary in relation to biblical interpretation, before situating Micah within current critical engagement with the book of the Twelve and focusing specifically on Micah's relation with Jonah and Nahum. The main body of the commentary is devoted to the interpretation and exegesis of Micah, engaging widely with theologians and biblical scholars. Gignilliat addresses literary issues involving the structure, grammar, and textual variants of given passages and - in keeping with the goals of the International Theological Commentary - provides analysis of Scripture's literal sense in relation to its theological subject matter. This volume offers scholars, clergy and lay readers alike a unique combination of critical exegesis and rigorous theological interpretation
Includes bibliographical references and indexes
Keywords: Bible -- Commentaries; Bible; Theology; Commentaries; Criticism, interpretation, etc; Bible ; Micah ; Commentaries; Bible ; Micah; Kommentar